Multi-stage metamorphism recorded in crustal xenoliths from Permian dykes of the region of Mrirt (Moroccan Central Massif). (October 2022) - Duchene, Stéphanie; Severac, Jean-Luc; Samalens, Nadège; Driouch, Youssef; Ntarmouchant, Ahmed; Kriegsman, Leo; Dahire, Mohamed; Debat, Pierre; Gouy, Sophie
Abstract: The Permian magmatic rocks from Morocco contain crustal xenoliths that sample the Variscan crust in a context of widespread magmatism. A series of such xenoliths was collected in Permian dykes of the Central Massif, in the region of Mrirt. The metapelitic xenoliths are silica poor to intermediate (44 < SiO2 <57 wt%) and alumina-rich (17 < Al2 O3  < 34 wt%) and are notably enriched in some HFSE (Nb, Ta, Ti) and some transition elements (Cr, V, W, Ni). Their petrographic evolution depicts a multi-stage evolution from an early, subsolidus, metamorphic history related to regional metamorphism, of which biotite, garnet and sillimanite are the witnesses toward a late thermal evolution coeval with the entrapment in the magma, marked by pervasive partial melting and development of peritectic spinel and cordierite together with K-feldspar and ilmenite. The overall presence of corundum, which relates to the high Al2 O3 content, accounts for an initial stage of partial melting and magma escape, prior to the entrapment in the magma. Textural and chemical observation suggests further xenolith digestion and melt flux from the xenoliths toward the magma during ascent. Thermodynamic modelling allowing the determination of the pressure-temperature history of each xenolith shows that the initial pressure varies from ca. 1.5 to ca. 6 kbar, which, considering lithostatic pressure, corresponds to sampling depths of ca. 5–25 km. The temperatures recorded by the parageneses coeval with partial melting in the presence of spinel are in the range 800–900 °C whatever the pressure, which accounts for rapid heating due to thermal equilibration with the magma. U–Th/Pb dating of monazite by EMPA gives a poorly resolved Permian age of 293 ± 25 Ma for metamorphism in the xenoliths, in accordance with the stratigraphic age of the host rock. The pressure conditions are similar to those recorded for regional metamorphism in the other Variscan outcrops in Morocco, namely the Jebilet, the Rehamna and the Aouli-Mibladen granitic complex, while the maximal temperatures are much higher. The xenoliths thus appear as typical of the Late Variscan geological evolution of the deep crust in the Moroccan Mesetas, where abundant magmatism was responsible for local crustal heating of a crust previously affected by regional metamorphism. Highlights: Metapelitic xenoliths sample Moroccan Variscan crust from 5 to 25 km depth. Xenoliths record a first stage of regional metamorphism. High-temperature metamorphism at low-pressure is due to xenoliths entrapment in the magma. EMPA monazite dating confirms the Permian age of the microgranodioritic dykes.